Seasonal determination of trace and ultra-trace content in Macrocystis pyrifera from San Jorge Gulf (Patagonia) by Total Reflection X-ray Fluorescence - Salomone, Vanesa Natalia (2017)
Seaweed have a great capacity to accumulate heavy metals in their tissues. The chemical characterization of seaweed is important due to their use in environmental monitoring and human or animal food. The aim of the present study was to evaluate the multi-elemental composition of seaweed from San Jorge Gulf (Patagonia, Argentina) by Total Reflection X-ray Fluorescence (TXRF). The elements As, Br, Cu, Cr, Fe, Mn, Ni, Pb, Rb, Sr, V and Zn were seasonally analyzed and quantified in blades of Macrocystis pyrifera. TXRF showed to be a suitable technique for simultaneous multi-element analysis in this kind of samples. The results revealed seasonal variations in the chemical content for some elements; arsenic content was maximum in summer and autumn, iron concentration increased to the winter and zinc concentration was maximum in autumn. The sum of principal micronutrients (Fe + Zn + Mn + Cu) varied between 114 and 171 mg k−1 g dw. The total As concentration ranged between 36 and 66 mg kg−1 . Lead, nickel and copper were not detected.